Identify Student Misconceptions Using Three Tier Diagnostic Instruments on Physical Fitness Materials SD Negeri Danasri Kidul 02 - Supriyanto Supriyanto; Wanda Nugroho Yanuarto; Subuh Anggoro (UM Purwokerto Press, 2025)
This research aims to identify the misconceptions of grade 6 students at SD Negeri Danasri Kidul 02 regarding physical fitness. The approach used is descriptive quantitative with a three-tier diagnostic instrument. This instrument reveals misconceptions through multiple-choice questions, reasons for answers, and students' level of confidence. The research subjects are all 15 grade 6 students (8 female and 7 male). Data is analyzed to examine the types of misconceptions, the frequency of their occurrence, and students' confidence in those misconceptions. The research results are expected to provide an accurate overview of students' misconception profiles. This information is important for designing more effective and targeted learning strategies. The three-tier instrument is considered important for an in-depth evaluation of students' understanding, beyond just right or wrong answers. This research also encourages the development of teaching materials to minimize misconceptions. Consequently, the conceptual understanding of physical fitness at the elementary school level can be improved.